The Effect of Brand Activation on Brand Awareness: Survey of Visitors to Teras Komuji Coffee Shop Bandung - Anas Aulia; Gitasiswara; Agus Sudono (Universitas Yapis Papua, 2023)
This study aimed to determine how the effect of brand activation on brand awareness at Teras Komuji. In this study, the independent variable (X) is brand activation, consisting of several sub-dimensions: identity, employee, product and service, and communication. The dependent variable (Y) is brand awareness. The type of research used is descriptive and verification with an explanatory survey method and a cross-sectional study approach. The data in the study used primary data from a sample of 220 respondents, namely customers who had visited and had activities at Teras Komuji. The data analysis technique used was multiple regression using the assistance of a statistical calculation program. The results showed that, together and separately, the brand activation variables significantly affected brand awareness at the Teras Komuji